Possible Correlations between Atherosclerosis, Acute Coronary Syndromes and COVID-19 - Grzegorowska, Oliwia (J Clin Med, 2020)
An outbreak of SARS-CoV-2 infection in December 2019 became a major global concern in 2020. Since then, several articles analyzing the course, complications and mechanisms of the infection have appeared. However, there are very few papers explaining the possible correlations between COVID-19, atherosclerosis and acute coronary syndromes. We performed an analysis of PubMed, Cochrane, Google Scholar, and MEDLINE databases. As of September 15, 2020, the results were as follows: for “COVID-19” and “cardiovascular system” we obtained 687 results; for “COVID-19” and “myocardial infarction” together with “COVID-19” and “acute coronary syndrome” we obtained 328 results; for “COVID-19” and “atherosclerosis” we obtained 57 results. Some of them did not fulfill the search criteria or concerned the field of neurology. Only articles written in English, German and Polish were analyzed for a total number of 432 papers. While the link between inflammatory response, COVID- 19 and atherosclerosis still remains unclear, there is evidence that suggests a more likely correlation between them. Practitioners’ efforts should be focused on the prevention of excessive inflammatory response and possible complications, while there are limited specific therapeutic options against SARS-CoV-2. Furthermore, special attention should be paid to cardioprotection during the pandemic.